Optimizing dehydration of apples Malus Domestica with fructo-oligosaccharide incorporation - Egea,Mariana Buranelo (2012)
The objective of the present study was to study the effect of the variables of the osmotic dehydration process on sliced Fuji apples (Malus domestica) using a 2 x 3² factorial design. The variables studied in the apple slices were the pretreatment (blanching or acidification), the temperatures (30, 45 and 60ºC) and the FOS concentration (40%, 50% and 60% m/v) of the osmotic solution. There was no difference among the pretreatments for the water activity and titratable acidity. The slices pre-treated by the acidification presented less enzymatic browning (greatest luminosity L* value) combined with a greater soluble solid contents (thus, this treatment was selected). Treatments T4 (45ºC and 40% m/v) and T7 (60ºC and 40%m/v), using the acidification presented responses within the recommended standards and FOS were validated by the repetition.